1996
DOI: 10.1128/mcb.16.2.704
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe pcr1+ Encodes a CREB/ATF Protein Involved in Regulation of Gene Expression for Sexual Development

Abstract: The Schizosaccharomyces pombe pcr1 gene encodes a bZIP protein that apparently belongs to the cyclic AMP response element (CRE)-binding protein/activating transcription factor family. The deduced pcr1 gene product consists of 171 amino acid residues and is most similar to the mammalian CRE-BP1. A glutathione S-transferase-Pcr1 fusion protein produced in Escherichia coli was able to bind specifically to the CRE motif in vitro. Analysis with anti-Pcr1 serum suggested that Pcr1 is included in the major CRE-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 59 publications
2
128
0
3
Order By: Relevance
“…Recent studies have indicated the presence of homologues of the transcription factors known to be CaMK-I substrates in mammalian cells (e.g. ATF1, CREB) (41)(42)(43)(44). Whether or not these are substrates for S. pombe CMK1 either in vitro or in vivo will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the presence of homologues of the transcription factors known to be CaMK-I substrates in mammalian cells (e.g. ATF1, CREB) (41)(42)(43)(44). Whether or not these are substrates for S. pombe CMK1 either in vitro or in vivo will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that Ptc1 may indirectly regulate Atf1, perhaps by dephosphorylating an Atf1 co-factor involved in transcriptional induction. It was recently shown that Atf1 forms heterodimers with the protein encoded by the pcr1 ϩ gene (28). ⌬pcr1 cells display a phenotype similar to ⌬atf1 mutant cells, suggesting that Atf1-Pcr1 heterodimers may have an important role in the stress-induced gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…This is not an unreasonable notion as c-Jun can recruit JNK to phosphorylate dimerization partners via specific docking interactions (Kallunki et al1996). At least three ATF family members have been identified in fission yeast in addition to Atf1, namely Pcr1, Atf21, and Cbp1 (Takeda et al 1995;Kanoh et al 1996;Shiozaki and Russell 1996;Watanabe and Yamamoto 1996;J.B.A. Millar and N. Jones, unpubl.…”
Section: A Model Of Stimulus-specific Gene Transcriptionmentioning
confidence: 99%